Knihovna stavebních prvků koaxiálního filtru pro CST Microwave Studio - Vorek, Jiří (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2010)
Tato práce se zabývá vývojem nástroje - maker usnadňující návrh koaxiálních dutinových rezonátorů. V práci je popsána problematika návrhu složitých struktur v CST Studio Suite 2009. Za tímto účelem jsou vytvořená makra poskytující hrubý a jemný model optimalizační rutině Tuning-Space Mapping.

This thesis deals with development of tool – macros which help to create coaxial cavity filters. It describes problematic design of complex structures at CST Studio Suite 2009. For this purpose macros supporting coarse and fine model to method Tuning – Space Mapping (TSM) was made. This means creating fine model at CST MWS and coarse model at CST DS.
Library of building elements of coaxial filters for CST Microwave Studio
Keywords: Tuning – Space Mapping; CST Studio; koaxiální dutinový filtr; jemný model; hrubý model; optimalizace; makra; elektromagnetický simulátor pole; Virtual Prototyping; Visual Basic; Pascal; Tuning – Space Mapping; CST Studio; coaxial cavity filter; the fine model; the coarse model; optimization; macros; electromagnetic field simulator; Virtual Prototyping; Visual Basic; Pascal